Optimizing process parameters for enhancing mechanical properties of aa6061 composites reinforced with walnut shell ash and silicon carbide - Rajesh Angirekula; S. Manickam; P. Ravindra Babu (Applied Engineering Letters)
Aluminium 6061 (AA6061) plays an important role in modern engineering due to its versatile applications, including aerospace, automotive, and construction. This study explores AA6061 as a matrix material reinforced with walnut shell ash (WSA) and Silicon Carbide (SiC), produced through the ultrasonic-assisted stir casting technique. The research aims to improve the process parameters using the Taguchi L9 orthogonal array. The parameters include weight percentage of reinforcement - 2% (1%WSA+1%SiC), 4% (2%WSA+2%SiC), and 6% (3%WSA+3%SiC), Stirring speed (SS) -300 rpm, 350 rpm, and 400 rpm, and Stirring time (ST) -2, 3, and 4 minutes. The response properties examined are hardness, impact strength, and compressive strength. Optimal parameters for achieving maximum hardness are 6% reinforcement, 300 rpm stirring speed, and 2 minutes of stirring time. For optimal impact strength, the best conditions are 2% reinforcement, 300 rpm stirring speed, and 2 minutes of stirring time. For maximum compressive strength, the ideal parameters are 6% reinforcement, 400 rpm stirring speed, and 3 minutes of stirring time. Scanning Electron Microscope (SEM) images confirmed the uniform distribution of reinforcements, supporting the results. This study demonstrates the impact of optimizing process parameters to improve the mechanical properties of AA6061 composites, contributing significantly to their potential applications.